2009
DOI: 10.4028/www.scientific.net/amm.16-19.1053
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Micromachining Using Thiobacillus Ferrooxidans Based on Different Culture Medium

Abstract: This paper presents a novel fabrication process for micro metal parts using biologic etching method. The sheet metal parts can be etched by metabolism and biochemical reaction of microorganism. Thiobacillus ferrooxidans (T. f.) was employed in the machining process of metal components. By this bio-etching method, several shims with a thickness of 0.1mm and a diameter of only 2mm with a thickness of 0.07 mm and a diameter of 15mm and 16mm were fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The surface quality deteriorated rapidly, and at the end of the 2 h, the surface roughness of the three kinds of materials reached the worst, and then became stable. Beyond the 2 h, it no longer increased significantly, but fluctuated within certain limits and then reached the stable stage eventually (Yang et al, 2009). …”
Section: The Process Of Biomachiningmentioning
confidence: 97%
See 1 more Smart Citation
“…The surface quality deteriorated rapidly, and at the end of the 2 h, the surface roughness of the three kinds of materials reached the worst, and then became stable. Beyond the 2 h, it no longer increased significantly, but fluctuated within certain limits and then reached the stable stage eventually (Yang et al, 2009). …”
Section: The Process Of Biomachiningmentioning
confidence: 97%
“…In another study, several shims with a thickness of 0.1 mm, a diameter of only 2 mm, a thickness of 0.07 mm, and diameters of 15 mm and 16 mm were fabricated using this biomachining method (Yang et al, 2009). In this study, the change in surface roughness was also investigated.…”
Section: The Process Of Biomachiningmentioning
confidence: 98%
“…The surface quality deteriorated rapidly, and at the end of the 2 h, the surface roughness of the three kinds of materials reached the worst, and then became stable. Beyond the 2 h, it no longer increased significantly, but fluctuated within certain limits and then reached the stable stage eventually [12].…”
Section: Elk Asia Pacific Journals -Special Issue Isbn: 978-81-930411mentioning
confidence: 98%
“…The researchers also found that the metal removal rate during biomachining was inversely proportional to the machining time but not simply linear. In another study, several shims with a thickness of 0.1 mm, a diameter of only 2 mm, a thickness of 0.07 mm, and diameters of 15 mm and 16 mm were fabricated using this biomachining method [12]. In this study, the change in surface roughness was also investigated.…”
Section: Elk Asia Pacific Journals -Special Issue Isbn: 978-81-930411mentioning
confidence: 99%
“…Acidithiobacillus ferrooxidans has been widely used in the bioleaching and indirect biomachining of copper . This bacterium utilizes the energy generated by oxidation of ferrous ions to ferric ions to fix carbon dioxide in the air (Eq.…”
Section: Introductionmentioning
confidence: 99%